Subconvulsant doses of pentylenetetrazol uncover the epileptic phenotype of cultured synapsin-deficient Helix serotonergic neurons in the absence of excitatory and inhibitory inputs - Brenes García, Oscar Gerardo (2016)
Synapsins are a family of presynaptic proteins related to several processes of synaptic functioning. A variety of reports have linked mutations in synapsin genes with the development of epilepsy. Among the proposed mechanisms, a main one is based on the synapsin-mediated imbalance towards network hyperexcitability due to differential effects on neurotransmitter release in GABAergic and glutamatergic synapses. Along this line, a non-synaptic effect of synapsin depletion increasing neuronal excitability has recently been described in Helix neurons. To further investigate this issue, we examined the effect of synapsin knock-down on the development of pentylenetetrazol (PTZ)-induced epileptic-like activity using single neurons or isolated monosynaptic circuits reconstructed on microelectrode arrays (MEAs). Compared to control neurons, synapsin-silenced neurons showed a lower threshold for the development of epileptic-like activity and prolonged periods of activity, together with the occurrence of spontaneous firing after recurrent PTZ-induced epileptic-like activity. These findings highlight the crucial role of synapsin on neuronal excitability regulation in the absence of inhibitory or excitatory inputs.